Global Financial and Economic Crisis and its Russian Manifestations - Goryunov A. P. (Prostranstvennaâ Èkonomika, 2009)
Main causes of the current global economic crisis are considered, whose major discrepancy lies in the total capital accumulated by the American economy exceeding the size of capital value, which could have been covered by the revenues of the economy itself